The Role of Smart city to Improve The Success of Surabaya City branding Based on Government’s Perspective - Shinta Permana Putri Putri (Universitas Medan Area, 2023)
Promoting the city by adopting branding techniques is one way to create a competitive city. In some literature it is stated that smart city initiatives can be an effective strategy in determining the success of city branding. This study aims to identify the role of smart city strategy in supporting the success of Surabaya city branding, which is known for its transformation into a smart city in Indonesia. This research is a qualitative research using content analysis method. Data collection was carried out through interviews with the relevant government. Based on this research it was found that according to the government's perspective, the implementation of smart city has a role in supporting the successful implementation of city branding in Surabaya. Substantially, smart city innovation is input for the message that Surabaya wants to convey through city brand ing efforts. From the implementation side, smart city innovation plays a role in achieving the goals, objectives and functions of Surabaya city branding which are carried out with interrelated stakeholders. In this case, the success of Surabaya's city branding cannot be separated from the success of smart city implementation, which has been running relatively long in this city. This research provides a new perspective on the government's role in developing smart cities as an effective city branding strategy and how smart cities can act as city branding.